Semantic Opposition “Sky - Earth” as Element of Artistic Space in B. L. Pasternak’s Novel “Doctor Zhivago” - W. Zou (Научный диалог)
The article is devoted to investigation of the role of the semantic opposition “sky - earth” in the novel by B. L. Pasternak “Doctor Zhivago.” The relevance of the topic is justified, firstly, by the need for a more thorough study of the peculiarities of the artistic space of a literary text; secondly, by the importance of the study of the influence of the author’s philosophical and religious views on the peculiarities of the art world of the works, on the specifics of the image of literary heroes, their images and personalities, interactions with each other. The contexts are analysed that contain the words nebo ‘sky,’ zemlya ‘earth,’ and other lexical representatives of the relevant concepts: verkh ‘top,’ niz ‘bottom,’ pole ‘field,’ les ‘forest,’ zvezdy ‘stars,’ etc. On the basis of the conducted analysis, the author argues that the semantic opposition “sky - earth” is one of the most important semantic elements of literary text of the novel. Images of sky and earth in the novel are interpreted with the aim to discover in them the Christian and pagan motifs. It is argued that these images participate in the organization of vertical and horizontal space of the novel. It is shown that the earthly and the heavenly in the novel are in dispute, constantly collide with each other. The author comes to the conclusion that however, despite the apparent opposition of these images, the protagonist of the novel does not seek to choose between the life of heaven or earth - he takes all aspects of life.